A new species of mite in the genus Ernogamasus Athias-Henriot, 1971 (Parasitiformes: Parasitidae) - Witaliński, Wojciech; Fenďa, Peter (Zootaxa, 2020)
A new mite species Ernogamasus papilio sp. nov., originating from south-eastern Poland and north-eastern Slovakia, is described, as well as a supplementary description for E. aliitectatus (Athias-Henriot, 1967).